Comparison of the trend of suicide before and after the COVID-19 pandemic in Southeast Iran from 2016 to 2023 - Ehsan Movahed; Asma Afsharmanesh; Hadiseh Aqarabi; Rasoul Raesi; Kiavash Hushmandi; Salman Daneshi (BMC Public Health)
Abstract Background Suicide, as one of the most important psychological consequences of the COVID-19 pandemic, can be a threat to public health. Understanding the changes in suicide rates before and after the pandemic provides insights into the psychological effects of such crises on communities. This study aimed to compare the trends in suicide and suicide attempt rates in Southeast Iran before and after the COVID-19 pandemic, covering the period from 2016 to 2023. Methods This descriptive-analytical study was conducted through a census method on 5676 individuals who attempted suicide from 2016 to 2023. Medical records of those who attempted suicide were collected from the integrated system of the Ministry of Health (SIB) during the specified years. The data was collected using a checklist and analyzed with descriptive and inferential statistical tests at the significance level of P < 0.05. Results The findings indicate a significant increase in suicide rates after the COVID-19 pandemic, with 61.8% of the total 5,676 cases occurring post-pandemic compared to 38.2% before. The most affected demographic was young adults aged 19 to 34, whose suicide rates increased by a factor of 9.8, while women experienced a notable rise of 28.2 times in suicide rates after the pandemic. Additionally, uneducated individuals had the highest suicide rates, with a dramatic increase of 35.8 times among illiterate individuals after COVID-19, highlighting the urgent need for targeted mental health interventions and support systems. Conclusion A significant increase in suicide rates after the COVID-19 pandemic, particularly among young adults and women, highlights the urgent need for targeted mental health interventions, especially for vulnerable groups such as housewives and single individuals. Additionally, the correlation between education levels and suicide rates underscores the importance of addressing educational disparities as part of comprehensive mental health strategies.